Smart Mobility and Social Exclusion From the Perspective of Young People - van Hove, Tomke; Koch, Jonas; Meyer, Christiane (Journal of Geography Education, 2025)
The Agenda 2030 and particularly the Sustainable Development Goal (SDG) 11 aim to achieve a sustainable and inclusive urban (development). Digital mobility services are seen as an expedient solution for this goal. However, they also involve the risk of social exclusion. This article presents the perspectives of young people on the digital mobility transition and their vision for a smart, inclusive mobility using the example of the city of Hanover in 2050. The results show that young people can be sensitized to social exclusion risks through focus group discussions and that the methodological approaches are suitable for a possible thematic approach in geography lessons.